2014
DOI: 10.1155/2014/168407
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Based Regulation of Cancer Cachexia

Abstract: Cancer cachexia, consisting of significant skeletal muscle wasting independent of nutritional intake, is a major concern for patients with solid tumors that affects surgical, therapeutic, and quality of life outcomes. This review summarizes the clinical implications, background of inflammatory cytokines, and the origin and sources of procachectic factors including TNF-α, IL-6, IL-1, INF-γ, and PIF. Molecular mechanisms and pathways are described to elucidate the link between the immune response caused by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 86 publications
2
132
0
3
Order By: Relevance
“…Previous studies have demonstrated that systemic inflammation, particularly NF-κB-evoked pro-inflammatory cytokine formation, plays a critical role in inducing muscle wasting by activating the UPS through inhibition of Akt activity and impairment of muscle differentiation and myogenesis [2729]. The levels of pro-inflammatory cytokines in the serum and NF-κB activation are dramatically increased in patients with cancer cachexia [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that systemic inflammation, particularly NF-κB-evoked pro-inflammatory cytokine formation, plays a critical role in inducing muscle wasting by activating the UPS through inhibition of Akt activity and impairment of muscle differentiation and myogenesis [2729]. The levels of pro-inflammatory cytokines in the serum and NF-κB activation are dramatically increased in patients with cancer cachexia [28].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models of cancer cachexia like the Apc Min/+ and C-26 adenocarcinoma implant models, have demonstrated a clear dependence on IL-6, with IL-6 signaling inhibition being able to attenuate cachexia progression [1, 2]. However, another widely used mouse implant model, Lewis Lung Carcinoma, has been equivocal related to IL-6 dependence [32].…”
Section: Il-6 Targeted Therapeutics: Progress In Preclinical Models Omentioning
confidence: 99%
“…Cancer cachexia is wasting syndrome that occurs in approximately 80% of cancer patients and is the primary cause of death for 22–30% of all cancer patients [1, 2]. A significant complication related to prevention of cachexia is that cancer patients are not usually diagnosed with cachexia until they have lost more than 5-7% of body mass [3, 4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several rodent models of cachexia and some human cancers, IL-6 is associated with the development of muscle wasting and body weight loss (6, 8, 19-21). Classical IL-6 signaling involves binding of the cytokine to the membrane-bound IL-6 receptor (mIL-6r) on target tissues, which include hepatocytes, immune cells, and skeletal muscle (22-24). mIL-6r is a heterodimer comprising the ligand-specific gp80 unit and the signal-transducing gp130 unit (25).…”
Section: Introductionmentioning
confidence: 99%